Genotype and Regrowth Interval Effects on In Situ Disappearance of Rhizoma Peanut - Sanchez, Joao M. D.; Vendramini, Joao M. B.; Silveira, Maria L.; Sollenberger, Lynn E.; Dubeux, Jose C. B.; Moriel, Philipe; Kuwahara, Frank A. [UNESP]; Cecato, Ulysses; Yarborough, James K.; Soares Filho, Cecilio [UNESP]; Leite de Oliveira, Fabio C. (Crop Science Soc Amer, 2018)
Rhizoma peanut (Arachis glabrata Benth.) is a widely used warm-season legume in Florida. Ecoturf is a rhizoma peanut germplasm with superior nutritive value; however, there is limited information about the effects of regrowth interval on this characteristic. The objective was to investigate the effects of regrowth interval on in situ crude protein (CP) and dry matter (DM) disappearance of Ecoturf compared with the predominant cultivar 'Florigraze'. The experiment was conducted from July to October of 2014 and 2015. Treatments were a split-plot design of Florigraze and Ecoturf (main plots) harvested at regrowth intervals of 4, 8, and 12 wk (subplots), distributed in a randomized complete block design with four replicates. Samples of each treatment were incubated in two steers (Bos spp.) for 0, 3, 6, 9, 12, 24, 48, and 72 h, and DM and CP disappearance were fit to a nonlinear model. Ecoturf had greater CP concentration than Florigraze (193 vs. 168 g kg(-1)). There was no effect of genotype on in situ effective disappearance of CP (715 g CP kg(-1)); however, there was a quadratic effect of regrowth interval. Ecoturf had greater effective disappearance of DM than Florigraze only at 4 wk of regrowth (597 vs. 563 g kg(-1)). Dry matter and CP disappearance parameters may differ between Ecoturf and Florigraze. Harvesting at a regrowth interval of 8 wk or less may improve rhizoma peanut nutritive value.